Strengthening The Capacity of Tunggularum Hamlet Community, In Optimizing the Lemongrass Plants into Essential Oil Products - Aprilia Fitriani; Nurul Hidayah; Liya Yusrina Sabila; Haris Imam Karim Fathurrahman (UKInstitute, 2026)
Tunggularum Hamlet, Wonokerto Village, Sleman Regency, has considerable potential in lemongrass cultivation, but its utilization remains limited to traditional uses such as seasoning and herbal drinks. This community service program aimed to strengthen community capacity in optimizing lemongrass into value-added essential oil products through socialization, training, and the provision of distillation equipment. The activities included discussions with partners, socialization on lemongrass essential oil processing and packaging, practical distillation training, and evaluation through questionnaires. The program involved lecturers, students, and approximately 20–25 community participants, predominantly women farmers and housewives. The results showed that the program positively improved participants’ knowledge, management skills, economic independence, and mindset regarding the business potential of lemongrass essential oil. Most participants reported sufficient knowledge improvement, slight increases in management capability and economic independence, as well as positive changes in their entrepreneurial mindset. In addition, participants highly appreciated the support provided by the community service team during the program. Overall, the program successfully enhanced community awareness and initial capacity in developing lemongrass essential oil businesses, although further mentoring and practical assistance are still needed to achieve sustainable economic impacts and stronger entrepreneurial readiness.